The Perspectives of Asylum Seekers When Accessing Sexual Health Services in Cork and Kerry. (20th October 2021) - Jones, MM; Barry, F; Davoren, M
Abstract: Objectives: The aim of this study is to gain an understanding of the collective experiences of asylum seekers when accessing sexual health services in Cork and Kerry so that this research may inform how future policies and service provision can be targeted towards addressing these specific needs. Specifically, the objective is to determine the perceived barriers and facilitators to accessing sexual health services among asylum seekers, and to get an understanding of the overall lived experiences of asylum seekers when accessing these services. Methods: This is a qualitative study which utilised data from 14 semi-structured interviews conducted with asylum seekers between May and June 2019. Participants were over 18 and living in direct provision in Cork or Kerry. This study used a content analysis to interpret the data and develop categories which produced the results. Results: Participants demonstrated varying levels of understanding of sexual health and sexual health services. Several barriers and facilitators were identified which can be grouped into socioeconomic, political/legal, systemic, and social/cultural/religious barriers and facilitators. Conclusions: The findings from this study highlighted several areas for improvement in the provision of information and services relating to sexual health for asylum seekers and revealed the importance of addressing these issues to fulfil the purpose of public health by promoting health, preventing disease and prolonging life for all members of society. Key messages: There are varying levels of knowledge around sexual health and access to services among asylum seekers in direct provision. There are several barriers and facilitators to sexual health and access to services among asylum seekers and these highlight the areas of improvement that can shape future policy and service provision.